Performance of Membrane with Poly(vinyl acetate) Modified by Starch - Hua Zhang, Yan; Gu, Jiyou; Shi2, Junyou; Di, Mingwei; Li, Zhiguo; Tan, Haiyan; Qiu, Si (Asian Journal of Chemistry, 2013)
The use of starch on poly(vinyl acetate) emulsion blend modified in order to achieve improved film toughness, which aims to improve water resistance and film-forming emulsion adhesive performance. Dynamic mechanical properties (DMA), scanning electron microscopy (SEM) method was used to analyze the dynamics of film emulsion blend composite mechanics, the distribution of latex particles and glass transition temperature. The results show that with pure poly(vinyl acetate) (PVAc) compared to starch-modified film-forming emulsion film distribution, glass transition temperature of the homopolymers emulsion up to 50 ºC.